Molecular Modelling Analysis of the Metabolism of Aspirin - HUQ, FAZLUL (Asian Journal of Chemistry, 2010)
In this study, molecular modelling analyses using molecular mechanics, semi-empirical and DFT calculations have been carried out to investigate the relative stability of aspirin and its metabolites. The results support the idea that the metabolites of aspirin, especially salicyluric acid, can be more toxic than the parent compound because of higher reactivity. It may cause glutathione depletion, thus compromising the antioxidant status of the cell.